Studi Komparasi Konsep Etika Guru dan Murid Menurut KH Hasyim Asy ari dan Ibn Jama'ah - Rejchan Hanafi (FAI, 2017)
Studi Komparasi Konsep Etika Guru dan Murid Menurut KH Hasyim Asy ari dan Ibn Jama'ah